Managing Radiotherapy Practice during Coronavirus Disease 2019 Pandemic: Medical Physicist's Perspective - Bhaveshwar Yadav; Gautam Sarma; Mithu Barthakur; Pranjal Goswami; Shachindra Goswami (Journal of Radiation and Cancer Research, 2020)
Coronavirus disease 2019 (COVID-19) has now become the largest global health issue. The World Health Organization on March 11, 2020, declared COVID-19 disease as a global pandemic. We have formulated certain strategies based on published evidences to help medical physicists to formulate their own protocols to carry out planning and treatment. Social distancing, sanitization, and segregation are crucial for all. Time, distance, and shielding are essential criteria for radiation safety and it remains unchanged for COVID-19 too, as quarantine time, social distancing, and face/body shielding are important.